The effects of intravenous anaesthetics on the cardiovascular system of the rabbit. - McGrath, J C (1977)
1 A pithed rabbit preparation is described that allows selective stimulation of the vertebral outflows. 2 The responses to stimulation of sympathetic vasopressor fibres were blocked by hexamethonium and phentolamine but potentiated by cocaine, whereas the responses to stimulation of cardioaccelerator fibres were blocked by propranolol. 3 Ketamine, althesin and pentobarbitone enhanced the effects of noradrenaline and attenuated the effects of sympathetic nerve stimulation. Thiopentone enhanced the effects of both noradrenaline and sympathetic nerve stimulation. 4 In pithed rabbits a transient, dose-related cardiovascular depression was produced by each agent irrespective of whether vasomotor tone was present whereas in decerebrate rabbits the corresponding cardiovascular depression was longer lasting. 5 It is concluded that the cardiovascular depression produced by intravenous anaesthetics in intact rabbits is due to a combination of central and peripheral effects.